Brand Extension Wardah: The Influence of Brand Image and Environmental Concern: JEL Classification: M31, D12, Q56, M14, L66 - Afifah Raudhatul Utami; Firman Firman (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Increasing consumer attention to environmental issues encourages companies to integrate sustainability into their marketing strategies, including through the development of sustainability-based brand extensions. In the beauty industry, Wardah implements this strategy through the Wardah Nature Series which carries the concept of Halal Green Beauty. This study aims to analyze the influence of environmental concern and brand image on attitude toward brand extension with brand extension fit as a mediating variable in Generation Z in Padang City. This study uses a quantitative approach with an associative design. Data was collected through the distribution of questionnaires to 138 Generation Z respondents in Padang City who had used Wardah products with purposive sampling techniques. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS software. The results of the study show that brand image has a positive and significant effect on attitude toward brand extension and brand extension fit. Environmental concerns have a positive and significant effect on brand extension fit, but do not have a significant effect directly on attitude toward brand extension. In addition, brand extension fit has a positive and significant effect on attitude toward brand extension and is able to mediate the influence of environmental concerns and brand image on attitude toward brand extension. These findings show that consumer acceptance of the Wardah Nature Series is not only influenced by concern for the environment and brand image, but also by the perception of conformity between the parent brand and the expanded product. Therefore, brand extension fit and a strong brand image are important factors in increasing consumer acceptance of sustainability-based brand extensions.